DECISION SUPPORT SYSTEM FOR PREDICTING EMPLOYEE LEAVE USING THE LIGHT GRADIENT BOOSTING MACHINE (LIGHTGBM) AND K-MEANS ALGORITHM - Vasthu Imaniar Ivanoti; Megananda Hervita P.; Gandung Triyono; Dyah Puji Utami (Jurnal Teknik Informatika (Jutif), 2023)
Nowadays, decision support systems have gained wide popularity not only in private companies but also in government sectors. These systems play a crucial role in assisting leaders during the decision-making process. The effective functioning of the government heavily relies on employee performance, which requires discipline in carrying out their duties and responsibilities. Employee discipline is closely linked to their attendance, including leave-taking. Therefore, analyzing employee leave data can reveal trends and interrelationships, providing leaders with valuable information and insights for determining employee leave policies. To address this issue, data mining applications such as the Light Gradient Boosting Machine (LightGBM) regression prediction model can be utilized. This model takes into account factors like gender, age, and the starting year of leave to predict the number of employees who take annual leave simultaneously with holidays. Additionally, clustering algorithms like K-Means can be employed to group reasons for leave into clusters, identifying common leave patterns among employees. In this study, employee leave application data from January 2018 to July 2022 was collected from the Leave module within the HRIS (Human Resource Information System) application. The research outcomes encompass a dashboard visualization presenting descriptive analysis and modeling using LightGBM. The modeling results yielded reasonably accurate predictions, as evidenced by model testing that showed a difference of only 1 employee. Additionally, K-Means clustering formed 4 clusters of leave reasons, with the majority being family-related, illness, childcare, and elderly care. The dashboard can be used by management as a consideration for approving employee leaves, ensuring well-planned leave scheduling for the following year and minimizing disruption to work execution in each department.